Safety of Concurrent Nasal and Oropharyngeal Surgery for Obstructive Sleep Apnea. (September 2014) - Banuchi, Victoria; Cohen, Justin C.; Kacker, Ashutosh
Objective: This study evaluated for increased complications or risk associated with concurrent nasal and oropharyngeal surgeries to treat patients with obstructive sleep apnea (OSA). Study Design: Retrospective chart review. Methods: We performed a retrospective chart review on consecutive patients between 2006 and 2011 who underwent either simultaneous nasal and pharyngeal surgery (group 1) or pharyngeal surgery alone (group 2) to treat OSA. We compared the length of hospitalization and the rate of complications in both groups. Results: Group 1 consisted of 20 patients, all male, with ages ranging from 25 to 72 years (average, 35 years) and apnea-hypopnea index (AHI) from 2.6 to 119 (average, 52.2). Group 2 consisted of 20 patients, 1 female, with ages ranging from 23 to 71 years (average, 37 years) and AHI from 10 to 101 (average, 46.1). In group 1, 30% of patients were ambulatory compared to 25% of patients in group 2. In all cases, the nonambulatory patients were observed for only 1 night. The rate of complications in both groups was 10% (2 out of 20 in each group). Both complications in group 1 were post-tonsillectomy bleeds. In group 2, 1 patient had a post-tonsillectomy bleed and 1 patient was readmitted with dehydration due to poor pain control. There was no statistically significant difference in length of hospitalization or rate of complications in these 2 groups. Conclusion: Performing concurrent nasal and oropharyngeal surgery for OSA was safe when compared to oropharyngeal surgery alone in our cohort and, with careful selection criteria, can even be done in the ambulatory setting. Large, multi-institutional investigations are indicated.